Development of a Portable Light Bulb Efficiency Test Kit A Case Study of Terminal 21 Shopping Mall Bangkok - Suksantidelok, Thawatchai; Pechkomkam, Saratool; Mayeetae, Harsun; Panawa, Niabdulloh; Ko-Uaychai, Pramook (Institute of Vocational Education Southern Region 3 Journal (KRIS Journal), 2024)
This research aimed to: 1) create and find the efficiency of a mobile light bulb efficiency test kit: a case study of Terminal 21 Shopping Mall, Bangkok and 2) study the users’ satisfaction towards a mobile light bulb efficiency test kit: a case study of Terminal 21 shopping mall, Bangkok. The target group of 14 people was selected through purposive sampling technique. The research instruments consisted of 1) a quality assessment form of a mobile light bulb efficiency test kit and 2) a questionnaire on the users’ satisfaction towards a mobile light bulb efficiency test kit. The research statistics included percentage, mean, and standard deviation. The research results revealed that 1) the developed mobile light bulb efficiency test kit can be used effectively. The evaluation results from the experts showed that the test kit was of high quality. In addition, 2) the users were highly satisfied with the test kit in overall.